Respon generasi z terhadap perkawinan beda agama di Indonesia Pasca SEMA Nomor 02 Tahun 2023 - Mardiana, Abdilah Reza (Maliki Interdisciplinary Journal, 2024)
Marriage is a sacred bond between two people to fulfill each other’s physical and spiritual needs. The existence of interfaith marriages in Indonesia is a frequent occurrence, requests for decisions to the court from couples of different religions are increasing, then SEMA Number 02 of 2023 concerning the Prohibition of Registration of Interfaith Marriages was born. However, is SEMA a solution and how will Generation Z as the nation’s next generation respond to this problem? So that is the background to the emergence of this article. To answer this question, this article contains Generation Z’s response to interfaith marriages using a questionnaire method that analyzes the law on interfaith marriages in Indonesia from the perspective of positive and religious law. The results of this article’s research are that many Generation Z people are of the opinion that marriage should be carried out with partners who have the same religion/belief and SEMA Number 02 of 2023 has not provided legal certainty regarding the prohibition on registering interfaith marriages in Indonesia.